2010
DOI: 10.1097/ta.0b013e3181beed96
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanics of Locked Plating for Repairing Proximal Humerus Fractures With or Without Medial Cortical Support

Abstract: Anatomic reduction with the medial cortical contact was the stiffest construct after a simulated two-part fracture. This study affirms the concept of medial cortical support by fixing proximal humeral fractures in varus, if absolutely necessary. This may be preferable to fixing the fracture in anatomic alignment when there is a medial fracture gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 65 publications
4
86
2
2
Order By: Relevance
“…Hence, mechanical support of the medio-inferior region of the humeral head seems to be essential for maintaining fracture reduction in locking plating of proximal humerus fractures [6]. Lescheid et al also confirmed in his biomechanical study the concept of medial cortical support by fixing two-part proximal humeral fractures, preferably in anatomic alignment [7]. However, those studies only observed the radiological and biomechanical evidence of medial support.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Hence, mechanical support of the medio-inferior region of the humeral head seems to be essential for maintaining fracture reduction in locking plating of proximal humerus fractures [6]. Lescheid et al also confirmed in his biomechanical study the concept of medial cortical support by fixing two-part proximal humeral fractures, preferably in anatomic alignment [7]. However, those studies only observed the radiological and biomechanical evidence of medial support.…”
Section: Introductionmentioning
confidence: 65%
“…Continuous varus stress of the rotator cuff may result in varus displacement of the humeral head and collapse of the articular surface during early rehabilitation, when the fracture fails to achieve anatomical reduction. Another recent biomechanical study by Lescheid et al demonstrated that locking plating with medial cortical support could exhibit higher biomechanical performance in a two-part proximal humerus fracture model [7]. Gardner et al also noted that the presence of medial support had a significant effect on the magnitude of subsequent reduction loss [6].…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, studies show that fractures treated with either anatomic reduction or screws in the inferomedial humeral head for which no medial column support was obtained had a high incidence of failure. 3,[9][10][11][12] An intramedullary fibular allograft used together with a locking plate fixation has been recently described in biomechanical studies to provide additional medial support and prevent varus malalignment. 13 The purpose of this study was to evaluate the clinical and radiographic outcomes of a locking plate with fibular allograft augmentation in unstable humeral fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical studies have also shown the importance of reconstruction of head-shaft angle. [19][20][21] Poor head-shaft angle reconstruction weakens the axial compressive strength, and axial compressive strength has a positive correlation with the degree of varus. A stable reduction and excellent function of shoulder joint depend on the quality of the reconstructed head-shaft angle.…”
Section: 18mentioning
confidence: 99%